Kualifikasi Guru berdasarkan 1 Tesalonika 2:7-12 - Ezra Tari (UIN Sunan Gunung Djati Bandung, 2020)
The author studies 1 Thessalonians 2: 7-12 about teacher qualifications. This study departs from the writer's anxiety about the condition of the teacher. Where teachers are currently required to perform tasks according to the educational qualifications of each level. But in reality, there are still many teachers who have not met the minimum bachelor requirements. One obstacle is the distance to go to college and the age that is not young anymore. As a result, many teachers have difficulty in accessing education. With that problem, the author examines the qualifications of teachers based on 1 Thessalonians 2: 7-12. The method used by the author is qualitative. The method used to trace the actual state of the object of research. The study used is exegese. Exegese tries to understand the text from various aspects. Based on the study conducted by the author in this paper, there are two important things that need to be learned, namely hospitality in love. And the example of struggle is an example for many people. Teaching is a very important task in Paul's ministry. Paul gave an example of how to work hard in work as a teacher, providing holistic service. This paper is a teacher qualification study that touches on nature that must be possessed by a teacher.